(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses changes in military education and training, the place and role of military pedagogy in military professional activities, the attitude of officers to ethics and discipline, the necessary qualities in the management of military units, issues of pedagogical and psychological impact on military personnel.